Gender Inequality and State Security: The Effects of Women’s Social Equality on Domestic Terrorism - Carter, Brittnee (Women & criminal justice, 2023)
Women’s roles in political violence and terrorism have largely been examined through the agent/victim dichotomy. We suggest that women’s social inequality contributes to both roles of women as victims and as perpetrators of terrorist violence, with both roles ultimately contributing to increases in supplies of domestic terrorism. Particularly, women’s social inequality contributes to terrorism in three ways: it normalizes violence in society, makes women susceptible to coercion from terrorist groups, and results in grievances in the female population that may mobilize them to violence. An in-depth case study of women in Somalia and the quantitative results both suggest that women’s political, economic, and social inequality are associated with higher levels of domestic terrorism. The results show that the impact of women’s social equality through balanced social exchanges in society subsumes the impact of vertical equality measures such as political and economic equality.